Handbook of farm, dairy, and food machinery - Kutz, Myer (William Andrew Pub., 2007)
Indispensable for food, chemical, mechanical, and packaging engineers, Handbook of Farm, Dairy, and Food Machinery covers in one comprehensive volume fundamental food engineering principles in the design of food industry machinery. The handbook provides broad, yet technically detailed coverage of food safety, regulations, product processing systems, packaging, facilities, waste management, and machinery design topics in a ̥farm to the fork̲ organization. The 22 chapters are contributed by leading experts worldwide with numerous illustrations, tables, and references. The book includes the new USDA regulations for ̥certified organic̲ processing, as well as state-of-the-art technologies for equipment both on the farm and in the plant.
Keywords: Food processing machinery -- Handbooks, manuals, etc.; Farm equipment -- Handbooks, manuals, etc.; Dairying -- Equipment and supplies -- Handbooks, manuals, etc.; elektronické knihy; electronic books